Periodontal treatment success rate in patients with history of systemic disease diabetes mellitus: Tingkat keberhasilan perawatan periodontal pada pasien dengan riwayat penyakit sistemik diabetes melitus - Mappangara, Surijana; Afrini, Nurul (Makassar Dental Journal PDGI Makassar, 2024)
Diabetes mellitus can affect the success rate of periodontal tissue treatment. The condition of DM in each individual is multifacto-torial. This literature review discusses the theoretical basis of the discussion of articles on the success rate of periodontal treat-ment in patients with DM by collecting and comparing several articles that discuss the success rate of periodontal treatment in patients with a history of DM. Several articles were found which showed that the success rate of periodontal treatment in pa-tients with a history of DM is influenced by many factors. It was concluded that the success of periodontal treatment in patients with a history of DM is influenced by the patient's glucose levels, bad habits, nutrition, socioeconomic status, and lifestyle.